Synthesis and Structural Characterization of Picolinoyl (4-ethylthiosemicarbazide) and its New Heteroleptic Cu(II) Complex - Huy, Nguyen Hung; Huy, Nguyen Gia; Nguyet, Trieu Thi; Thang, Pham Chien (VNU Journal of Science: Natural Sciences and Technology, 2022)
The ligand picolinoyl(4-ethylthiosemicarbazide) HL was synthesized by the reaction of picolinohydrazide and ethyl isothiocyanate in absolute ethanol. The structure of HL was characterized by spectroscopic methods such as IR, 1 H, and 13 C NMR spectroscopy. One-pot reaction of CuCl 2 and equimolar amounts of HL and o -phenanthroline in CH 2 Cl 2 /MeOH mixture with the presence of a supporting base like pyridine gave rise to a new heteroleptic cationic Cu(II) complex with the composition of [Cu(L)( o -phen)] + . Crystalline PF 6 – salt was obtained after workup with ( n -Bu 4 N)(PF 6 ) and single-crystal structure of the complex was determined. The spectroscopic data and X-ray crystallography demonstrated that the Cu(II) ion is five-coordinate with the coordination sphere consisted of ( S , N 1 , N pyridine ) and ( N , N ) donor sets belonging to the singly deprotonated ligand L – and o -phenanthroline, respectively.